Aspects of Wellbeing for Indigenous Youth in CANZUS Countries: A Systematic Review - Kate Anderson; Elaina Elder-Robinson; Alana Gall; Khwanruethai Ngampromwongse; Michele Connolly; Angeline Letendre; Esther Willing; Zaine Akuhata-Huntington; Kirsten Howard; Michelle Dickson; Gail Garvey (International Journal of Environmental Research and Public Health, 2022)
Indigenous children and young people (hereafter youth) across CANZUS nations embody a rich diversity of cultures and traditions. Despite the immense challenges facing these youth, many harness cultural and personal strengths to protect and promote their wellbeing. To support this for all youth, it is critical to understand what contributes to their wellbeing. This review aims to identify components contributing to wellbeing for Indigenous youth in CANZUS nations. Five databases were searched from inception to August 2022. Papers were eligible if they: focused on Indigenous youth in CANZUS nations; included views of youth or proxies; and focused on at least one aspect of wellbeing. We identified 105 articles for inclusion (Canada n = 42, Australia n = 27, Aotearoa New Zealand n = 8, USA n = 28) and our analysis revealed a range of thematic areas within each nation that impact wellbeing for Indigenous youth. Findings highlight the unique challenges facing Indigenous youth, as well as their immense capacity to harness cultural and personal strengths to navigate into an uncertain future. The commonalities of Indigenous youth wellbeing across these nations provide valuable insights into how information and approaches can be shared across borders to the benefit of all Indigenous youth and future generations.